PENGARUH PERILAKU BERLEBIHAN DALAM PENGGUNAAN INTERNET DAN KONTROL DIRI TERHADAP CYBERBULLYING PADA REMAJA DI KOTA BANDUNG - Astriningsih Wahyudi, - (2021)
The purpose of this study is to determine the effect of excessive internet use and self-control against cyberbullying in teenager in the Bandung city. This study uses a quantitative approach with correlation model. The sampling technique used in this study is convenience sampling to capture 199 appropriate respondents. The instruments used in this research are Theory and measurement of generalized problematic Internet use: A two-step approach to measure excessive internet use behavior, High Self-Control Predicts Good Adjustment, Less Pathology, Better Grades, and Interpersonal Success to measure self-control, and The Cyberbullying Questionnaire (CBQ) to measure cyberbullying. The data analysis technique that use is Spearman correlation. The results show that excessive internet use behavior has no effect on cyberbullying, while self-control has an effect on cyberbullying. In addition, research shows that only self-control contributes to cyberbullying